Effect of ketoconazole and diltiazem on the pharmacokinetics of apixaban, an oral direct factor Xa inhibitor - Frost, Charles E.; Byon, Wonkyung; Song, Yan; Wang, Jessie; Schuster, Alan E.; Boyd, Rebecca A.; Zhang, Donglu; Yu, Zhigang; Dias, Clapton; Shenker, Andrew; LaCreta, Frank (British journal of clinical pharmacology, 2015)
Aim Apixaban is an orally active inhibitor of coagulation factor Xa and is eliminated by multiple pathways, including renal and non‐renal elimination. Non‐renal elimination pathways consist of metabolism by cytochrome P450 (CYP) enzymes, primarily CYP3A4, as well as direct intestinal excretion. Two single sequence studies evaluated the effect of ketoconazole (a strong dual inhibitor of CYP3A4 and P‐glycoprotein [P‐gp]) and diltiazem (a moderate CYP3A4 inhibitor and a P‐gp inhibitor) on apixaban pharmacokinetics in healthy subjects. Method In the ketoconazole study, 18 subjects received apixaban 10 mg on days 1 and 7, and ketoconazole 400 mg once daily on days 4–9. In the diltiazem study, 18 subjects received apixaban 10 mg on days 1 and 11 and diltiazem 360 mg once daily on days 4–13. Results Apixaban maximum plasma concentration and area under the plasma concentration–time curve extrapolated to infinity increased by 62% (90% confidence interval [CI], 47, 78%) and 99% (90% CI, 81, 118%), respectively, with co‐administration of ketoconazole, and by 31% (90% CI, 16, 49%) and 40% (90% CI, 23, 59%), respectively, with diltiazem. Conclusion A 2‐fold and 1.4‐fold increase in apixaban exposure was observed with co‐administration of ketoconazole and diltiazem, respectively.